(untitled) (Revista Inclusiones, 2020)
This article examines approaches to the problem of assessing and evaluating competences, methods and mechanisms for measuring results of the educational program 44.03.05 – “Pedagogical Education”, the specialization “Biology and Chemistry” in a particular regional university environment. The study has established that competences play the main role as the final result of education in the real educational process within the competency based approach, while educational technologies serve for the formation of these competences. Evaluation tools, assessment technologies and evaluation procedures serve as a means of the claimed results proof. The application of the competency based approach in the educational process is closely connected with the problem of assessing students’ competence. Competency and competence are able to act as the main systemforming factors, which unites the activity of various departments of the university or teaching modulars (subjects) within a particular educational institution. Our educational program of the educational program “Pedagogical Education”, being a methodological system for applying the ideas of the competency based approach, is aimed at solving problems in the field of professional activity, since it is focused on the formation of the methodological student competence while being one of the approaches to assess and evaluate students’ competences.